Current Concepts Review: Evaluation and Management of Posterior Hip Pain. Issue 17 (1st September 2018) - Gómez-Hoyos, Juan; Martin, Robroy L.; Martin, Hal David
Abstract : Understanding the etiology of and evolving research on intra- and extra-articular hip complaints requires comprehensive diagnosis and management of the spectrum of posterior hip diseases. Interest in posterior hip disorders has increased in recent years as new studies and theories have emerged regarding the disease process. Although most of the differential diagnoses around the posterior hip have traditionally been considered uncommon, recent reports suggest that these complaints have instead been commonly overlooked. Failure to identify the cause of posterior hip pain in a timely manner can increase pain perception, deteriorate the patient's hope, and consequently affect quality of life. Posterior hip pain could be differentiated as intrapelvic and extrapelvic, and differential diagnosis is made based on a comprehensive history, physical examination, and imaging studies. Plain radiography, CT, MRI, 3T MRI, and imaging-guided injection tests are usually necessary for accurate diagnosis. Surgical intervention, whether endoscopic or open, is required for patients with long-standing symptoms for whom nonsurgical treatment has been unsuccessful and who have experienced temporary relief of their symptoms after injection. Orthopedic surgeons are uniquely trained in understanding the anatomy, biomechanics, clinical evaluation and treatment of all five layers of the hip.